Genetic, hereditary and congenital diseases in buffaloes: are they a limiting factor for the buffalo development in Latin America? - William Gomes Vale (Revista Científica)
Along with the exponential growth of the buffalo population in Latin America (12 percent annually), for a population of 6 million head, the problems derived from inbreeding have increased as the national herd, estimated at 3.0 million heads by the Brazilian Association of Buffalo Breeders, come from just over 200 imported animals. Importing animals from the Asian continent was suspended in 1956 for sanitary reasons (rinderpest). 1962, this prohibition was broken, and some buffaloes were brought from India. After that date, there was no official importation of genetic material from Asia; it was only in 1989 that some animals of the Mediterranean, Murrah, and Jafarabadi breeds were imported from Italy and Bulgaria, and currently, semen of Murrah and Jafarabadi breeds have not been imported from any country. Genetic, hereditary, and congenital disabilities, complete or partial, are characterized by abnormalities in the structure and/or function of tracts or organs, complete system or parts of them. These problems have been identified in Brazil and other countries of Latin America (Vale, 1998; Damé, 2013), where more than 40 cases of different simi-lethal and lethal cases have been diagnosed, which were for the first time scientifically studied and published discribing the presence of undesirable genes in buffaloes due to the inbreeding existing in the buffalo Brazilian population. On the existence of inbreeding problems in buffalo herds in Brazil, many authors claimed the leading cause of the reduced number of animals that gave the origin of the different herds (the founder element) of the different breeds was composed of a reduced number of animals imported from the origin countries. Therefore, proof of genetic origin is necessary since most hereditary diseases are transmitted by recessive genes, which must be identified due to the extreme importance of animal production in every domes-tic species. While it becomes difficult to identify and eliminate animals carrying these genes due to the high cost resulting from the laboratory for diagnosis and animal elimination, the problem has been neglected and is continuously spreading and increasing. Once such problems occur in any animal species, those abnormalities/diseases must be identified since it is essential to determine the occurrence, prevalence, epidemiology, clinical symptoms, pathology, and distribution of the genes observed among the population, which must be screened in order to subsequently identified of kinship and set up a development control strategies through the use of breeding animals proven to be free of these undesirable genes, in order to control and eliminate such kind of diseases.